A novel route of synthesising Fe–W–B alloy powders and characterisation thereof. (8th August 2017) - Li, Cheng; Yang, Guoping; Liu, Ying; Qiu, Yuchong; Li, Jun
ABSTRACT: A novel method to synthesise sub-micron FeWB powders is proposed, by which pure-phase FeWB powders with a particle size of ∼500 nm were successfully obtained. This method consists of three steps: water atomisation, annealing treatment and acid dissolution of the matrix. Systematic characterisation was carried out throughout the preparing process to determine the detail phase evolution, chemistry features as well as the changes in particle size. It was found out that the as-atomised powders consisted of only α -Fe solid solution where W and B atoms are dissolved as solute atoms. And the annealing treatment could facilitate the precipitation of W and B atoms from the matrix to form tiny dispersive continuous net-like precipitates. Analyses showed that Fe6 W6 C, Fe3 W3 C and FeWB were precipitated in sequence during the annealing process. And following the chemical treatment, the α -Fe matrix and surface oxide layers could be completely removed and FeWB powders could be successfully recovered.